Pembelajaran Jarak Jauh Masa COVID-19: Strategi Guru Meningkatkan Kreativitas Anak Usia Dini - Muallifatul Khorida Filasofa, Lilif; Istianawati, Hani (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2021)
oronavirus Disease (COVID-19) causes learning to be done remotely from home. Distance Learning is a new thing in the world of education, especially Early Childhood Education (ECE). Children's creativity in early childhood learning is important to be maximized to reduce delays in achieving child development. This paper aims to see how the teacher's strategy in increasing children's creativity in distance learning. This research uses a qualitative research type. The data sources of this study were (1) Primary data sources, namely the principal, class teacher, and 5 students' parents. (2) Secondary data sources, namely supporting data that presents general data such as online articles, previous research, and books. Technique of data collection using observation, documentation, and interviews. Data analysis was carried out using the concept developed by Miles and Huberman, consisting of data reduction, data display, and concluding. The results showed that the strategy used by the teacher in the Implementation of Distance Learning at TK IT An-Nahl used several applications, namely: Google Meet, playing youtube videos and working on worksheets. Children's creativity at TK ITAn-Nahl can be done by creating works of art, imagination, exploration, experimentation, projects, and language. Factors that influence children's creativity in TK IT An-Nahl, namely: mental stimulation, mood, the role of parents, the role of teachers, and finances. The findings of this study contribute to an understanding of how the strategies used by teachers are to increase early childhood creativity during the COVID-19 pandemic.